Association between CD31 expression and histopathologic features in stage IB squamous cell carcinoma of the cervix. Issue 2 (1st March 2006) - Silva-Filho, A L; Traiman, P.; Triginelli, S. A.; Reis, F. M.; Pedrosa, M. S.; Miranda, D.; Abreu, E. S.; Macarenco, R.; Cunha-Melo, J R
Abstract : This study was undertaken to evaluate the association between the expression of CD31 in the tumor and the histopathologic findings in patients with carcinoma of the cervix. This study included prospectively 30 women, aged 46.6 ± 10.7 years, with stage IB squamous cell carcinoma of the cervix submitted to radical hysterectomy from November 2001 to September 2002. Samples from the tumor were taken and immunohistochemically evaluated by a monoclonal antibody for CD31. Clinicopathologic characteristics such as stage, tumor size, grade of differentiation, lymphatic vascular space invasion (LVSI), parametrial involvement, and status of pelvic lymph nodes were also recorded. The clinical stage (FIGO) was IB1 in 22 patients (73.3%) and IB2 in 8 patients (26.7%). The expression of CD31 was significantly associated with tumor size and the presence of LVSI, but not with grade of differentiation and vaginal or parametrial involvement ( P = 0.03, P = 0.032, P = 0.352, P = 0.208, and P = 0.242, respectively). On univariate analysis, the presence of pelvic lymph node metastasis was influenced by LVSI ( P = 0.003) and CD31 expression ( P = 0.032). However, on multivariate analysis, the presence of LVSI ( P = 0.007) was the only independent predictor of pelvic lymph node metastasis. The CD31 expression in tumor is significantly associated with LVSI and tumor size in patients with early-stage squamous cell carcinoma of the cervix.